If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7h-65=6h-35
We move all terms to the left:
7h-65-(6h-35)=0
We get rid of parentheses
7h-6h+35-65=0
We add all the numbers together, and all the variables
h-30=0
We move all terms containing h to the left, all other terms to the right
h=30
| 23−4q=11 | | 41/4-q=23/4 | | -3(y-5)=42 | | 1/3x7= | | b+44=9b-76 | | -4y+9=-3(27+3) | | 12x+6-2x+12=72 | | 12f+49=31f-84 | | 78f-46=33f+89 | | 13q-75=2q+79 | | 10x-6x-4-1=x-12+2x+2x | | 6x*x=92 | | -4(m−72)=-60 | | 10x-6x-4-1=x-12+ | | 42=17+5j | | 1.5e+-6= | | 27p+18=24p+21 | | 11k-48=7k-32 | | 14q+73=19q-7 | | 1.5e+-6=0 | | 5(2x+8)=-21+31 | | 9v+76=21v-44 | | 4|x+23|+26=18 | | 10x-2x-3-9=x-12+3x+3x | | 4||x+23||+26=18 | | 4(-5x+-7)=168 | | 3w-24=w+76 | | -8+12y-24=14y-63+5 | | 4f+11=99 | | 8k+99=19k+55 | | 16k+23=17k+21 | | 5n=-200 |